2013
DOI: 10.1016/j.jacc.2013.03.082
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Novel 3-Dimensional Electrocardiographic Mapping of Atrial Tachycardias by Invasive Mapping and Ablation

Abstract: This prospective multicenter series shows a high success rate of ECM in accurately diagnosing the mechanism of AT and the location of focal arrhythmia. Intraprocedural use of the system and its application to atrial fibrillation mapping is under way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 17 publications
0
57
0
1
Order By: Relevance
“…51 Inverse potential map is already being applied to analyze complex arrhythmias and has great potential to generate personalized ablation strategies. 52 The anatomic volume conductor models required to perform inverse potential map can also be used for preparing a patient-specific procedural roadmap (Figure 4).…”
Section: New Challenges: Competitive Methodsmentioning
confidence: 99%
“…51 Inverse potential map is already being applied to analyze complex arrhythmias and has great potential to generate personalized ablation strategies. 52 The anatomic volume conductor models required to perform inverse potential map can also be used for preparing a patient-specific procedural roadmap (Figure 4).…”
Section: New Challenges: Competitive Methodsmentioning
confidence: 99%
“…27 Based on the inverse principle, the clinical utility of non-invasive body surface mapping in atrial and ventricular arrhythmias has been reported. [28][29][30][31] Body surface mapping is undertaken by using a commercially available system (ECVUETM, Cardioinsight Technologies). After acquiring 64 section multi-detector CT images with a vest of 252 body-surface electrodes positioned on the thorax and upper abdomen, epicardial unipolar electrograms are reconstructed on a patient-specific biatrial geometry.…”
Section: Non-invasive Body Surface Mapping Analysis For Atrial Fibrilmentioning
confidence: 99%
“…Further in 92 % of cases, the mechanism of atrial tachycardia was accurately diagnosed. 27 In a feasibility study by Haissaguerre et al, ECGI was demonstrated to identify active sources of AF with high resolution. 28 Specifically, they demonstrated active sources in the vicinity of the pulmonary veins in patients with paroxysmal AF and more widespread sources in patients with the more sustained form of the arrhythmia.…”
Section: Advances In Imaging Techniques For Af Ablationmentioning
confidence: 99%